The Analysis of Computerized Accounting Practicum: Study Case of Faculty of Economic, Universitas Catur Insan Cendekia - Aditya Kurniawan Chandra; Sudadi Pranata; Gilang Putratama; Aan Kanivia; Mohammad Umar Fakhrudin (ITScience (Information Technology and Science), 2023)
The purpose of this study is to analyze and compare whether the computerized accounting laboratory is in accordance with computerized accounting practices in the work environment to support teaching and learning activities. The subjects of this study are Kantor Jasa Akuntan Langgeng, accounting lecturers, and accounting students. This is a qualitative study with a case study approach. The data collection techniques used for this study were interviews and observation. Based on the research that has been done, similarities between the two computerized accounting practices were found. The similarities found are from the workflow in general, such as data collection and database creation. Meanwhile, during the pandemic, learning can be done using online methods and also using blended learning methods.